Conulariid test microstructure and mineralogy - Ford, Robert C. (Kansas State University, 2011)
Conulariids are one of the most enigmatic groups of fossil organisms, and have been stimulating debates since the late 19th century. Many major questions remain; for example, three independent researchers (Babcock and Feldman, 1986b; Oliver and Coates, 1987; Van Iten, 1992b) reported three different mineralogies for the conulariid test within a six-year period, and are not known to have reached an agreement. Conulariid morphology is also debated, and many workers seem unable to agree on the basic architecture of the test or how it grows. Conulariid workers have also attempted to determine the taxonomic classification of conulariids, especially whether they have cnidarian affinities or occupy their own phylum. My work attempts to clarify some of these issues, as well as determine whether any morphological variation exists within single species of conulariids in different paleoenvironments. To this end, I have collected and prepared specimens for examination by scanning electron microscopy, transmitted polarized light microscopy, energy-dispersive spectrophotometery, and x-ray defractometry. Results include evidence for the presence of organic matrix in the conulariid test microstructure, the presence of three types of lamellae in the test, and support for carbonate-rich apatite [Ca5(PO4,CO3)3(OH,F)] mineralogy. Details of the test microstructure add further support for a coronatid scyphozoan affinity. The conulariid species examined here displayed no microstructural or mineralogical variation between different paleoenvironments (unless two of the species are actually environmental varieties, which seem unlikely).
Keywords: Conulariid; Microstructure; Lamella; Mineralogy; Internal carina; Transverse rib; Geology (0372); Paleocology (0426); Paleontology (0418)